HCF and LCM

Tagged: 

This topic contains 1 reply, has 2 voices, and was last updated by  Tarit Goswami 5 months, 1 week ago.

Viewing 2 posts - 1 through 2 (of 2 total)
  • Author
    Posts
  • #21570

    Pinaki Biswas
    Participant

    If HCF(a,b)=1, then prove that LCM(a,b)=ab.

    #21578

    Tarit Goswami
    Participant

    Well, we know from childhood that, gcd(a,b )*lcm(a,b)=ab. From here, as, gcd(a,b)=1 we will have lcm(a,b)=ab.

    • This reply was modified 5 months, 1 week ago by  Tarit Goswami.
    • This reply was modified 5 months, 1 week ago by  Tarit Goswami.
Viewing 2 posts - 1 through 2 (of 2 total)

You must be logged in to reply to this topic.